PENGARUH SUMBER DAYA MANUSIA, SISTEM PENGENDALIAN INTERN, TEKNOLOGI INFORMASI, DAN PEMAHAMAN BASIS AKRUAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi pada Organisasi Perangkat Daerah Provinsi Banten) - Melati Ramadhani; Ayu Noorida Soerono; Windu Mulyasari (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This study aims to determine the effect of the competence of human resources, internal control systems, utilization of information technology, and an understanding of accrual based government accounting system for quality of local government financial reports Province Banten. The approach used in this study is the quantitative approach. Data used in this study are primary data. Questionnaire submitted to the90 employees of the OPD Province Banten who works in finance /accounting, as many as 82 questionnaires (91.1%) returned, 16 questionnaires (19.5%) can not be processed, and 66 questionnaires (80.4%) can be processed. The data collected were processed using SPSS 20 software program. The statistical method used to test the hypothesis is multiple linear regression analysis. The results showed that the competence of human resources, internal control systems, utilization of information technology, and an understanding of accrual based government accounting system has a positive and significant impact on the quality of local government financial reports.